Buckling Analysis of Single-Layer Graphene Sheets Using Molecular Mechanics - Genoese, Alessandra; Genoese, Andrea; Rizzi, Nicola L.; Salerno, Ginevra (Frontiers in Materials, 2019)
The paper presents a nonlinear buckling analysis of single-layer graphene sheets using a molecular mechanics model which accounts for binary, ternary and quaternary interactions between the atoms. They are described using a geometrically exact setting and by the introduction of Morse and cosine potential functions, equipped with an appropriate set of parameters. We examine the critical and post-critical behaviours of graphene, under compression in the zigzag and in the armchair directions, and shear. Our findings show the suitability of standard thin-plates theory for the prediction of simple critical behaviours under various edge constraint conditions.